Comparative Analysis of Real Estate Investment Strategies for Retail and Qualified Investors - Horský, Matouš (2025)
This thesis analyzes the performance gap between Czech retail and qualified investor real estate funds. The theoretical section outlines the regulatory framework under ZISIF, investor segmentation, and real estate investment strategies. The practical part models two representative portfolios, each comprising Polish logistics and office assets, using standardized assumptions to assess return and risk profiles. Results indicate that qualified investor funds outperform retail funds, driven by higher leverage and development exposure, though with increased volatility. The analysis also examines fee structures, cash flows, and capital allocation across investor types. Key modeling challenges include limited transparency and data availability. Findings highlight the importance of aligning fund structure with investor sophistication and strategic flexibility.